Negative effective permeability of multilayers of ordered arrays of metal-dielectric nanosandwiches - C. Tserkezis; N. Stefanou; G. Gantzounis; N. Papanikolaou (Proceedings of SPIE, 2009)
We present a thorough theoretical study of the optical properties of periodic structures built of silver and silica nanodisks in a sandwich-like configuration, by means of full electrodynamic calculations using the extended layer-multiple-scattering method. The strong coupling of the metallic nanoparticles and the resulting plasmon hybridization lead to collective electric and magnetic resonant modes, which can be tuned by changing the structural parameters, such as nanoparticle size and lattice constant. We analyze the response of single- and multi-layer architectures of ordered arrays of such nanosandwiches on a dielectric substrate to externally incident light and evaluate the corresponding effective permittivity and permeability functions. Our results reveal the existence of optical magnetism, with a strong negative effective permeability over a tunable spectral range at near-infrared and visible frequencies. We introduce the complex photonic band structure as a tool in the study of three-dimensional metamaterials and establish additional criteria for the validity of their effective-medium description. Our work demonstrates the efficiency of the recently developed extended layer-multiple-scattering method in the study of metamaterials of composite metal-dielectric particles of arbitrary shape.